In Vitro Susceptibilities of Bordetella pertussis and Bordetella parapertussis to Two Ketolides (HMR 3004 and HMR 3647), Four Macrolides (Azithromycin, Clarithromycin, Erythromycin A, and Roxithromycin), and Two Ansamycins (Rifampin and Rifapentine) - Hoppe, Jörg E. (American Society for Microbiology, 1998)
When tested by agar dilution on Mueller-Hinton agar supplemented with 5% horse blood, the ketolides HMR 3004 and HMR 3647 were slightly more active (MIC at which 90% of the isolates were inhibited [MIC(90)], 0.03 μg/ml) against Bordetella pertussis than azithromycin, clarithromycin, erythromycin A, and roxithromycin. Azithromycin (MIC(90), 0.06 μg/ml) was the most active compound against B. parapertussis. Rifampin and rifapentine were considerably less active.